Beispiel Nr: 04
$ \text{Gegeben: } \text{ Punkt } A(xa/ya) \qquad \text{ Scheitel } S(xs /ys) \\ \text{Gesucht:} \\ y=ax^{2}+bx+c \\ \\ \text{Scheitel und Punkt}\\ \textbf{Gegeben:} \\ A(-\frac{1}{2}/0)\qquad \text[ Scheitel } S(2/3) \\\\ \\ \textbf{Rechnung:} \\ A(-\frac{1}{2}/0)\qquad S(2/3) \\ \text{Punkt A und Scheitel S in die Scheitelform einsetzen}\\ y=a(x-xs)^2+ys \\ 0=a(-\frac{1}{2}-2)^2+3 \\ 0=6\frac{1}{4}\cdot a+3 \qquad /-3 \qquad /:6\frac{1}{4} \\ a=\frac{0-3}{6\frac{1}{4}} \\ a=-\frac{12}{25} \\ y=-\frac{12}{25}(x-2)^2+3 \\ y=-\frac{12}{25}(x^2 -4 x+2^2)+3 \\ y= -\frac{12}{25}x^2+1\frac{23}{25}x+1\frac{2}{25} $